Burnout - Vrettos, Adrienne Maria (New York : Margaret K. McElderry Books, 2011)
Months after coming out of alcohol and drug rehab, high school student Nan wakes up on the subway the day after Halloween wearing a torn Halloween costume, her long hair cut, and "HELP ME" scrawled across her chest, feeling sick and having no idea how she got there.
810
Keywords: Drug abuse -- Juvenile fiction; Alcoholism -- Juvenile fiction; Emotional problems -- Juvenile fiction; New York (N.Y.) -- Juvenile fiction